Evaluation of Implanted Stent Occlusion Status Based on Neointimal Tissue Bioimpedance Simulations. (5th December 2019) - Portillo-Anaya, J. M.; Pérez, P.; Olmo, A.; Huertas, G.; Yúfera, A.
Abstract : This paper describes the characterization of the light hole, also known as the lumen, in implanted stents affected by restenosis processes using bioimpedance (BI) as a biomarker. The presented approach will enable real-time monitoring of lumens in implanted stents. The basis of the work hereby reported is the fact that neointimal tissues involved in restenosis can be detected and measured through their impedance properties, namely, conductivity and permittivity. To exploit these properties, a 4-electrode setup for BI measurement is proposed. This setup allows study of the influence of the various tissues involved in restenosis fat, muscle, fibre, and endothelium, together with the blood, on the BI value at several frequencies. In addition, BI simulation tests were performed using the electric physics module available in COMSOL Multiphysics®. Interestingly, fat constitutes the most influential layer on the value of impedance (measured in k Ω / μ m—magnitude change per micrometre of lumen occlusion). A case study using a standard stent is also presented. In this study, where the involved tissues and blood were simultaneously considered, we conducted an analysis for stable and vulnerable plaques in restenosis test situations. In this regard, the proposed method is useful to test the stent obstruction and detect potential dangerous cases due to nonstable fat accumulation.